Development of microwave reflected type moisture meter for wooden cross-arms - Ng, Kok Cheong (2000)
A simple, cheap, accurate, portable and easy to operate microwave reflected type moisture meter has been developed to determine the moisture content and consequently to assess the quality of the in service wooden cross-arms. The investigation shows that the dielectric properties of the Chengal wood are dependent on the moisture content (MC) at microwave frequencies. The moisture in wood contributes in two different forms, one below fiber saturation point (FSP) and the other above FSP. Both dielectric constant and dielectric loss factor for Chengal wood increases slowly when the Me increases from zero up to FSP and increases rapidly with MC above FSP. Investigation was made to find the optimum conditions for the sensor design. The optimum condition for best sensitivity of the sensor was determined through experimental and theoretical methods. It was found out that the sensitivity can be controlled by thickness of protective cover and the optimum thickness is about 1 mm. The investigation to find out the minimum thickness of the cross-arms section to avoid interference was discussed. It was found that the minimum thickness for the cross-anns to reach a semi-infinite length was about 50mrn. The operating principles of the sensor are based on the plane wave propagation theory and the dielectric mixture theory. The details of Weiner's mixture model were discussed and it was used as the theoretical model to predict and convince the experimental results. In the actual service condition, moisture content of Chengal wooden cross-arms varied within certain range. For decayed wood, its MC varying between Equilibrium moisture content (EMC) to about 45% of dry basis and the sound wood MC between EMC to about 30% of dry basis. It was quite hard for the cross-arms to achieve higher level ofM C. Once the cross-arms achieve a higher level ofMC, it may take about 20 hours to return to EMC level. The densities of severely decayed, partly decayed and sound wood were different from each other even from the same species of wood. The densities were found to vary between 680kgm-3 to 820kgm-3. The reflected power signal for severely decayed, partly decay and sound wood at EMC were less than 0.05, 0.05 to 0.10 and 0.13 to 0.15 respectively. It was found that the microwave reflected type sensor can determine the decay stage of the wooden cross arms at EMC. A HP-basic program was written to develop the meter scale for microwave moisture meter. The meter scale contains two types of reading. They are MC reading and stage of decay reading. The mean error were 2.3% and 1.1% for severely decayed and sound wood respectively and the maximum error were found to be 5.4% and 3.9% respectively.